Prediksi Tingkat Kepuasan Pelayanan Online Menggunakan Metode Algoritma C.45 - Yuni Indah Lestari (Jurnal Informatika Ekonomi Bisnis, 2021)
Online service is a service that uses the help of the internet. This service can solve various types of business without having to meet directly with employees. This can be done quickly and on time. Especially when we are currently experiencing the Covid-19 pandemic, all existing services are carried out online and this is increasingly being done by many parties, because they can maximize in helping people's affairs online. This service makes it easier for the public to register which will be done online during this pandemic. The data that will be processed in this online service from 2019 to 2020 is about data about people who do not understand online services, negative community responses, positive community expectations. The method used in this study is the method with the C4.5 algorithm where this is one of the algorithms that will be used to determine a classification or group of data and will be predictive. The advantage of this algorithm is that it can produce a decision tree which will make it easier to implement and will have an acceptable level of accuracy. The results of this study are able to predict a value or determine the level of community satisfaction in 2021 appropriately. Therefore, this study can be used as a reference to determine the level of satisfaction at the Padang City Population and Civil Registration Office. The method used in this study is the prediction method using the C4.5 algorithm by using as many as 14 attributes. The data used in this study is sourced from data from online questionnaires and stored in the Disdukcapil database which has as many as 50 community data which have been presented in a CSV file. The analysis in this study uses the help of tools in the form of rapid miner software version 5.3,000. The results of this study are that there are 3 rules from the data processing process using the C4.5 algorithm where the rule is the final result of the decision tree form.